Åland as a Special Case: From Monolith to Diverse? - Nihtinen, Atina Laura K. (Journal of Northern Studies, 2018)
The present article discusses two sets of issues. On the one hand, I consider the different factors and circumstances which have influenced relations between Swedish and Finnish on Åland and the implications of political change. On the other hand, I discuss the ways in which these are understood and presented in history writing. By considering continuity and change in history writing and language discussions I argue that history writing has changed from a rather monolithic interpretation rooted in nationalism and the early decades of autonomy towards a more versatile interpretation (such as considering Åland as being connected to both east and west and ideas such as many Ålands). At the same time the role of Swedish remains important, both as a matter of continuity (history) and as a matter of its instrumental function.